Sharia boards, managerial strategies and governance practices in Islamic banks: a Goffmanesque discourse - Karbhari, Yusuf; Benamraoui, Abdelhafid; Sheikh Hassan, Ahmad Fahmi (Emerald Publishing, 2023)
Purpose: The study applies Erving Goffman's (1974) “frame analysis” principles to examine how Sharia governance is practiced in Islamic banks and explores the interaction and strategies adopted by bank managers to influence the decisions of Sharia scholars. The study also aims to identify inherent flaws in the Sharia compliance review system. Design/methodology/approach: The study employs the principles of Goffman as a lens to critically analyse a rich dataset obtained through interviews undertaken with 46 key players operating in the governance framework of the Malaysian Islamic banking industry due to its progressive Islamic governance framework. Findings: The study demonstrates that managers of Islamic banks may engage in “passing” and “covering” strategies while interacting within the governance structure. Concurrently, Sharia boards (SBs) implement “protective practices” during their interactions, adding complexity to their responsibilities within the banks. Consequently, SBs cannot merely be viewed as instruments for legitimising banking operations. This raises questions about the “impression management,” “concealment” and “competence” strategies employed by managers and SB members, as suggested by Goffman's framework. These findings indicate that there is room for further enhancement in the governance practices of Islamic banks. Research limitations/implications: Future research could explore aspects related to the governance of Islamic banks, such as investigating the independence and effectiveness of internal Sharia officers. Examining the strategies employed during their interactions with external Sharia boards and other stakeholders could provide further valuable insights. Practical implications: By highlighting shortcomings in the governance and compliance review process, the findings could serve as a valuable resource for policymakers. The insights derived could inform the development of regulations aimed at reducing opportunistic behaviour and promoting accountability in the Islamic banking sector. Originality/value: This study uniquely employs Goffman's concepts of “frontstage” and “backstage” strategies to offer insights into the interactions between Islamic bank managers and SBs and the impact of these interactions on Sharia compliance. The study contributes to the understanding of the dynamics between key players in the governance of Islamic banks and the factors influencing their adherence to Sharia principles.